Additional Analysis Of Employee Income On Civil Servant Loyalty with Job Satisfaction as an Intervening Variable at The North Tapanuli Regency Agriculture Office - Sartika Krisna Panggabean; Elfitra Desy Surya; Husni Muharram Ritonga (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study examines the influence of Employee Income Allowance (TPP) on the loyalty of Civil Servants (PNS), with Job Satisfaction as an intervening variable in the North Tapanuli Regency Agriculture Office. The study used the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach with the help of SmartPLS 3.0 software and involved 117 civil servant respondents to analyze the measurement model and structural model. The results of the outer model analysis showed that all indicators of TPP, Job Satisfaction, and Civil Servant Loyalty had an outer loading value above 0.70, with Cronbach's Alpha values ranging from 0.865 to 0.916, Composite Reliability between 0.902 to 0.937, and Average Variance Extracted (AVE) between 0.649 to 0.749, indicating convergent validity and adequate reliability. The discriminant validity test also shows that each indicator has the highest correlation with its own construct. Structural model evaluation showed that TPP had a positive and significant effect on Job Satisfaction (β = 0.895; T = 50.010; p < 0.001) and directly had a positive effect on civil servant loyalty (β = 0.576; T = 4,713; p < 0.001). In addition, Job Satisfaction has a positive effect on Civil Servant Loyalty (β = 0.364; T = 3.055; p = 0.003). Indirect influence analysis showed that TPP also significantly affected civil servant loyalty through job satisfaction (β = 0.326; T = 2,967; p = 0.004), which confirms that Job Satisfaction plays a role as a partial intervening variable. The R² value of 0.801 for Job Satisfaction and 0.840 for Civil Servant Loyalty indicates a strong explanatory ability of the model.